Sense of dwelling in disaster relocation: Temporary and public recovery housings after the 2011 earthquake in Japan - Kuroishi, Izumi (International Planning History Society Proceedings, 2018)
This study examines people's displacement in Kesennuma and Rikuzentakata cities in Japan during the last 6 years from the earthquake in 2011 in order to inquire the factors of the sense of dwelling in disaster relocation. By examining how the relocations of houses impact on people’s identity, what kind of social issues arose in the process, and how designing houses integrated with their community planning is essential to create a sense of belongings, it aims to explain how the idea of disaster relocation and social housing system should be reframed to adjust to the contemporary social issues. By comparing cases, I will explain how people keep striving to maintain their normal lifestyle, and how it is essential to create smooth integration between private and public space, and to help their own subjective engagement in the reconstruction of community in each stage of their relocations. In the era of displacement due to disasters, we need to reconsider the idea of house as the locus for people's identity and to reframe the idea of social housing and urban planning comprehensively and in process-oriented manner.